Smart cat feeder - Abdul Malik, Norjasween; Mas’aud, Nurul Hanna; Mohd Zainuddin, Nur Fatihah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Stray cats are often referred to as "community cats" normally can be found on the street. People enjoy providing food and water to stray cats, but they frequently leave it on the floor or on the road street. Hence, the food may be contaminated with bacteria, exposing them to various infections and health issues, such as food poisoning. The objective of this project is to develop a smart device that are equipped with various features that allow users to schedule and monitor the cat’s feeding times and portion size. This smart feeder cat has two main parts, which are food storage & drinking water storage. The food storage section employs the mechanical engineering idea of dynamic rotation. The food is then automatically set out within the predetermined timer using an actuator. Timer, with help of sensor and solar are innovated to this project to help user determine an appropriate feeding plan for the cats. Thus, food will always keep fresh and clean. Result and testing show that this smart feeder is functioned well. As solar power is a pollution-free and renewable energy source, make this product is an ecofriendly solution and more sustainable choice. As conclusion, this product is practical to be used, and it is expected to make sure that the health of the stray cats in safe hands and reduced the exposure to infections.